2002
DOI: 10.4269/ajtmh.2002.66.542
|View full text |Cite
|
Sign up to set email alerts
|

High levels of IgG4 to Schistosoma mansoni egg antigens in individuals with periportal fibrosis.

Abstract: Abstract. Specific IgG4 and IgE responses to adult worm antigen and soluble egg antigen (SEA) were examined in 267 individuals from an area in which schistosomiasis mansoni is endemic. Based on information obtained from clinical and sonographic examinations of this sample, the individuals were divided in three groups:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
1
27
0
2
Order By: Relevance
“…3136 It has been argued that this characteristic infection curve reflects the inability of the immature immune system of children and teenagers to eliminate the parasite. 18,19,21 Evaluation of the IgE and IgG4 anti-SEA reactivity over time showed that after 2005 anti-SEA IgE reactivity was significantly increased for both infected and uninfected individuals. Webster et al 37 showed that higher IgE serum levels among individuals living in endemic areas are a consequence of persistent antigen exposure, which is consistent with our observation.…”
Section: Discussionmentioning
confidence: 99%
“…3136 It has been argued that this characteristic infection curve reflects the inability of the immature immune system of children and teenagers to eliminate the parasite. 18,19,21 Evaluation of the IgE and IgG4 anti-SEA reactivity over time showed that after 2005 anti-SEA IgE reactivity was significantly increased for both infected and uninfected individuals. Webster et al 37 showed that higher IgE serum levels among individuals living in endemic areas are a consequence of persistent antigen exposure, which is consistent with our observation.…”
Section: Discussionmentioning
confidence: 99%
“…The DRB1*0901 allele was also associated with susceptibility to PSHD (OR = 2.14, 95%CI = 1.31-3.48, P = 0.002). The possibility that the HLA-DRB1*0901 allele is primarily responsible for PSHD susceptibility is an interesting point to be considered because IgG4 elevation has been found in individuals with the HLA-DRB1*0901 allele [66] and is positively linked to several systemic fibrosis conditions [67] and schistosomiasis peri-portal fibrosis [68]. It is probable that patients with HLA-DRB1*0901 are prone to produce B cells for specific…”
Section: Discussionmentioning
confidence: 99%
“…Vale lembrar que os anticorpos contra os ovos e os vermes adultos, especialmente da classe IgG, cursam com níveis séricos mais elevados naqueles pacientes com EM que apresentam fibrose periportal e esplenomegalia (24) . Além disso, a carga parasitária encontra-se relacionada com a evolução para as diversas formas da EM.…”
Section: Discussionunclassified
“…Adicionalmente, no artigo sobre a fibrose na hepatite C, descreveu-se correlação da fibrose hepática não apenas com os níveis de IgG, mas também com os de IgA e com o nível sérico total das imunoglobulinas (24) . Já no estudo sobre a fibrose na hepatite B, observou-se correlação tanto com os níveis de IgG como com os de globulinas e com a contagem de plaquetas no sangue periférico, mas não foi detectada com os níveis de IgA (19) .…”
Section: Discussionunclassified